AKULTURASI MAKNA ARSITEKTUR ISTANA KERAJAAN KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU (Interaksi Simbolik West-Turner) - Netri Falariza; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Acculturation is the process of mixed two cultures or more which elements of culture native still looks and is not lost. While culture are one of the essential basis in human life. In that culture contained values, thinking pattern, ethics, wisdom, regiositas, behavior and the pattern the interaction that followed by human beings and forming them. Culture that was found in an area variegated and varies,because of the nature of that culture himself reaches down from generation to generation from generation. The culture that is belived to be from a long. Used as the rituals that continuos and has only been done by each generation. Alcuturation meaning architecture a royal court Kecamatan Rokan IV Koto the Koto it is actually is the part a royal court Kecamatan Rokan IV Koto, achitectur of a royal court Kecamatan Rokan IV Koto this in fact taken from Minang culture since we have made the sign of the change at that architacture worn out there has just been architecture that originated from a culture of melayu.Research on acculturation culture in architecture a royal court Rokan sub district fourth quarter of this year the Koto this is the field study and research of literature that qualitative. The purpose of this research in order to understand the culture elements anywhere i like he complaining that affects architecture a royal court Rokan and the form of the acculturation on architecture a royal court here on wednesday and Thursday.The results of the study show that the acculturation the meaning of architecture a royal court Rokan sub district fourth quarter of this year the Koto this, a very dreadful mass of having the form of architecture that patterned different from what is mentioned,A royal court Rokan also has meaning and the effect on the community in Kecamatan Rokan IV this impurities.Keyword: Tradition, Interaksi Simbolik.